PORNOGRAFI YANG (TIDAK) CABUL: GENDER DAN SEKSUALITAS - Alma Wulandari (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2020)
Pornography is taboo and immorality that is present by the role of qualified technology. However, pornography on the contrary develops into works that are deliberately made to be brought into heat; its contents are not merely writing. Hendri Yulius in his book CAB*L: Perbincangan Serius tentang Seksualitas Kontemporer (2019), leads us to see pornography as a medium to study the devel-opment and socio-cultural dynamics of society. As well as being a documentation of human fan-tasy and contributing in drawing and influencing the way humans think about the conversation about sex(uality) and its practice. This paper will discuss how pornography contributes to the per-spective of humans about their sexuality and others.Keywords: Sexuality, Pornography, Popular Culture, Immorality, Sex.